2019
DOI: 10.22603/ssrr.2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Surgical Treatment for Arachnoid Web: A Case Series

Abstract: Introduction: We describe 5 patients who underwent operative treatment for arachnoid web (AW) and discuss the postoperative clinical outcome in each case. AW is an extremely rare disease that causes cord compression and syringomyelia in the thoracic spine. To date, 14 cases only of AW have been reported, and the effect of surgical intervention on clinical and radiologic outcomes is unknown. Methods: Five patients who underwent surgical treatment for AW were retrospectively reviewed. The clinical outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…As for the treatment of AW, all cases reported in the literature were treated surgically. The surgical treatment is removal of the AW after dural incision, with no fixation or decompression [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the treatment of AW, all cases reported in the literature were treated surgically. The surgical treatment is removal of the AW after dural incision, with no fixation or decompression [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nisson et al reported that, after surgery, 91% of patients showed neurological improvement [ 8 ]. On the other hand, Hirai et al showed that the postoperative symptoms tended to improve in 5 cases, but numbness of the lower limbs remained in 3 cases, and bladder disorders did not change after operation in 1 case [ 6 ]. At this time, there are no clear reports on the risks of postoperative residual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…10 also found the scalpel sign in all patients with arachnoid web. 8 , 10 Other advanced MRI techniques have been used in evaluation of arachnoid web. Thin arachnoid bands webs could be identified on high-resolution 3D T2 myelographic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…57 It has been hypothesized that arachnoid webs may be idiopathic, remnants of a previous arachnoid cyst that ruptured, or are precursors to arachnoid cysts that have not fully walled off. 3 , 5 , 6 , 8 Arachnoid adhesions could also result secondary to trauma or prior surgery. 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation